Workplace bullying, psychological perspectives and industrial relations : towards a contextualized and interdisciplinary approach - Hoel, Helge (2006)
Examines definitions of workplace bullying and explores less orthodox approches within a British context. Focuses primarily on managers as perpetrators. Comments on the bullying organization, the relevance of human resource management and of gender. Examines the issue within the UK public sector environment.